Fabrication and characterization of Chitosan Nanocarriers for Erucin Delivery Using Ionic Gelation Techniques - Ali Jalil Mjali (Universitas Negeri Malang, 2026)
Background: The incorporation of nanotechnology and bioactive molecules represents a boundary in modern pharmacology, aiming to improve the bioavailability and stability of plant-derived chemicals. This study focuses on the evolution of a novel drug delivery system using chitosan nanocarriers to encapsulate erucin, a potent isothiocyanate derived from Eruca sativa known for its significant anticancer, anti-inflammatory, and antimicrobial properties. Methods: Fresh chopped Eruca sativa leaves were macerated in water to get erucin phytochemical by enzymatic conversion with myrosinase , followed by an organic solvent extraction using dichloromethane. In the production of nano erucin, sodium tripolyphosphate -a cross-linker - was used in a process called ionic gelation. Three definite solutions were prepared with chitosan-to-erucin ratios of 0.5:1, 1:1, and 1.5:1. Then, centrifugation performed to purify the resulting nanoparticles which were characterized using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), and Zeta potential analysis to evaluate morphology, elemental composition, and surface charge, respectively